1995
DOI: 10.1177/109019819502200109
|View full text |Cite
|
Sign up to set email alerts
|

Examining a Paradox: Does Religiosity Contribute to Positive Birth Outcomes in Mexican American Populations?

Abstract: A particularly interesting and consistent finding regarding the health of the Latino population is that Mexican American women, despite their relatively lower socioeconomic status, deliver significantly fewer low birth weight babies and lose fewer babies to all causes during infancy than do women of other ethnic groups. A central thesis of this discussion is that the religiosity and spirituality of many of these Latinas, a key factor in their culture, may protect them and their infants through the pre- and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 18 publications
2
43
0
1
Order By: Relevance
“…Significant variables for this model included the coping strategies of solving family problems, seeking spiritual support, investing in close friends, and being humorous, and the self-perceptions of athletic ability and the importance of physical appearance. Spirituality and family orientation have been found to be cultural values for this ethnic group (Magana & Clark, 1995;Plante et al, 1995;Samaan, 2000), and the current study confirms the importance of these factors for school-age children. Children with higher levels of acculturative stress, which encompasses racial/cultural discrimination, may rely on family and religion rather than peer acceptance (perceived to be significantly lower by Latinos than by Whites), which may be less available because of discrimination.…”
Section: General Model Of Achievementsupporting
confidence: 91%
See 1 more Smart Citation
“…Significant variables for this model included the coping strategies of solving family problems, seeking spiritual support, investing in close friends, and being humorous, and the self-perceptions of athletic ability and the importance of physical appearance. Spirituality and family orientation have been found to be cultural values for this ethnic group (Magana & Clark, 1995;Plante et al, 1995;Samaan, 2000), and the current study confirms the importance of these factors for school-age children. Children with higher levels of acculturative stress, which encompasses racial/cultural discrimination, may rely on family and religion rather than peer acceptance (perceived to be significantly lower by Latinos than by Whites), which may be less available because of discrimination.…”
Section: General Model Of Achievementsupporting
confidence: 91%
“…These coping strategies can be conceptually divided into two different categories: (a) social support coping strategies, which are externally based (developing social support, solving family problems, seeking spiritual support, seeking professional help, being humorous, and religious coping strategies) and (b) self-supporting coping strategies, which may not require social interaction (developing self-reliance and optimism, avoiding problems, engaging in demanding activity, relaxing). Latino children used social support-based coping strategies significantly more often than White children, a finding consistent with the collectivist, family-oriented cultural values of this group (Magana & Clark, 1995;Plante et al, 1995;Samaan, 2000;Smart & Smart, 1995).…”
Section: Use Of Coping Strategiessupporting
confidence: 70%
“…For Latina Mexican Americans, religion, particularly Catholicism, may be more integrated in their identities because of the strong cultural connection to the virgin of Guadalupe within Mexico. 20,33 Latinas of Mexican origin might also be more connected to family members in Mexico because of the migrant nature of their jobs or the travel of family members and relatives across the border. In the United States, Puerto Ricans are the second largest subgroup of Latinos.…”
Section: Edwards Et Almentioning
confidence: 98%
“…Latinas can have fatalistic beliefs and misconceptions about cancer, such as divine predetermination as a cause [7, 4447], which impede use of cancer screening exams [35, 44, 48–50]. Religiosity involves beliefs, behaviors, and personal devotion [51], and is a key facet of Latino culture that promotes health behaviors [52]. Some studies have shown that church attendance is related with a healthier dietary and physical activity [53] and BC screening among Latinas [35].…”
Section: Introductionmentioning
confidence: 99%